Freemason Symbolism in European Landscape Gardens - Szabadics, Anita (4D Journal of Landscape Architecture and Garden Art, 2006)
The article explores the impact on European garden design by the secret society of Freemasonry, which played a determining role in the mindset of the Enlightenment. A large portion of the creators and proprietors of landscape gardens were lodge members, thus the society’s system of symbols and signs can often be discovered in the gardens. In order to comprehend these gardens it is essential to study Masonic symbolism.
Keywords: Europe; Freemasonry; landscape garden